(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the job satisfaction of medical staff at Hanoi General Hospital of Traditional Medicine in 2021 and some related factors. Subjects and Methods: A cross-sectional descriptive study on 200 medical staff working at Hanoi General Hospital of Traditional Medicine. Results: The mean score of satisfaction of medical staff was 3.42 ± 0.28. The overall satisfaction rate for health workers’ work was 49.0 %, of which professional improvement has the highest rate of satisfied health workers at 56.5% and the lowest was the management mechanism with 43.0%. There is a statistically significant relationship between the main income factor in the family and the average monthly income with the satisfaction of health workers with OR 0.52 and 1.98, respectively (p<0.05). Conclusions: The level of job satisfaction of health workers was quite good, in the next time it is necessary to take positive measures to increase income and improve the working environment towards achieving higher employee satisfaction.